2020
DOI: 10.3390/cancers12040863
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Imaging Reveals Neutrophil Defensins as Additional Biomarkers for Anti-PD-(L)1 Immunotherapy Response in NSCLC Patients

Abstract: (1) Background: Therapeutic blocking of the interaction between programmed death-1 (PD-1) with its ligand PD-L1, an immune checkpoint, is a promising approach to restore the antitumor immune response. Improved clinical outcomes have been shown in different human cancers, including non-small cell lung cancer (NSCLC). Unfortunately, still a high number of NSCLC patients are treated with immunotherapy without obtaining any clinical benefit, due to the limitations of PD-L1 protein expression as the currently sole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…Matrix-assisted laser desorption and ionization (MALDI) MSI can be used to determine both low-mass molecules and proteins in FFPE tissue [10,11]. However, analysis of lipids has proven difficult in this type of tissue due to their depletion during initial processing with organic solvents, which is further compounded by the remaining lipids being implicated in cross-binding with other structures in the tissue [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Matrix-assisted laser desorption and ionization (MALDI) MSI can be used to determine both low-mass molecules and proteins in FFPE tissue [10,11]. However, analysis of lipids has proven difficult in this type of tissue due to their depletion during initial processing with organic solvents, which is further compounded by the remaining lipids being implicated in cross-binding with other structures in the tissue [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, three peptides m/z 3369.5, m/z 3440.6 and m/z 3484.6 have found to be discriminative between a responding and a nonresponding NSCLC patient towards anti-PD-(L)1 immunotherapy, shown in Figure 1 [21].…”
Section: Detection Of Amps In Their Native Statementioning
confidence: 99%
“…Based upon this, the corresponding amino acid sequence can be determined and the precursor ion can be identified [17]. Even if the AMPs have a cyclic nature, due to their cysteine bond formation, mass spectrometry can be used as an identification tool, although a specific approach is needed [18][19][20][21]. The added benefit of using proteomic approaches to study AMPs is the fact that the majority of AMPs are post-or co-translational proteolytically processed from their large polyprotein precursor, resulting in the release of the active AMP.…”
Section: Introductionmentioning
confidence: 99%
“…The correct identification of the tumor origin is an important aspect in the personalized medicine field [ 38 ]. Recently, our research group reported the use of MALDI mass spectrometry imaging to measure therapeutic response in NSCLC patients who received immunotherapy [ 39 ]. MSI analysis was performed on pre-treatment FFPE biopsies and differential analysis revealed neutrophil defensin 1, neutrophil defensin 2 and neutrophil defensin 3 as predictive biomarkers for the response to immune-checkpoint-based immunotherapy in NSCLC patients.…”
Section: Maldi Mass Spectrometry Imaging In Cancer Researchmentioning
confidence: 99%
“…These outcomes were verified with immunohistochemical analyses specific for these neutrophil defensins and after pathological scoring of neutrophil defensin expression on different cell types, statistical analysis exposed a significant association between neutrophil defensin expression and a positive immunotherapy response. This is of major importance for immunotherapy decision, for a better quality of life for the NSCLC patient, to avoid treatment of patients who are not likely to respond and to reduce unnecessary treatment costs [ 39 ].…”
Section: Maldi Mass Spectrometry Imaging In Cancer Researchmentioning
confidence: 99%